A Review on Securing Audio Watermarking System using Discrete Fourier Transform for Copyright Protection (International Journal of Current Engineering and Technology, 2015)
The recent growth in pc networks, and a lot of specifically, the planet Wide internet, copyright protection of digital audio becomes a lot of and a lot of necessary. Digital audio watermarking has drawn in depth attention for copyright protection of audio information. A digital audio watermarking may be a method of embedding watermarks into audio signal to point out genuineness and possession. Our technique supported the embedding watermark into audio signal and extraction of watermark sequence. We tend to propose a brand new watermarking system victimization separate Fourier remodel (DFT) for audio copyright protection. The watermarks area unit embedded into the best outstanding peak of the magnitude spectrum of every non-overlapping frame. This watermarking system can provides robust lustiness against many styles of attacks like noise addition, cropping, re-sampling, re-quantization, and MP3 compression and achieves similarity values starting from thirteen sound unit to twenty sound unit. Additionally, planned systems attempting to realize SNR (signal-to-noise ratio) values starting from twenty sound unit to twenty-eight sound unit.
Keywords: Audio Segment; Discrete Fourier Transform (DFT); Signal-to-noise-ratio (SNR)